Comparison Of The Similarities And Differences Between The KTSP (2006) Curriculum, The 2013 Curriculum, The Merdeka Curriculum, And The 2025 Curriculum - Anisah; Novita Fatmasari (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to analyze the similarities and differences among the 2006 School-Based Curriculum (KTSP), the 2013 Curriculum, the Merdeka Curriculum, and the 2025 Curriculum (Deep Learning) by examining their characteristics, objectives, learning competencies, assessment systems, and the roles of teachers and students. This study employed a qualitative descriptive approach using a literature review method. Data were collected from books, scientific journal articles, government regulations, and other relevant academic sources. The collected data were analyzed through comparative content analysis to identify the development, continuity, and transformation of curriculum policies in Indonesia. The findings indicate that each curriculum reflects different educational priorities and approaches. The KTSP (2006) emphasizes school autonomy in curriculum development, while the 2013 Curriculum focuses on character education and scientific learning. The Merdeka Curriculum provides greater flexibility through differentiated learning and competency-based education. Meanwhile, the 2025 Curriculum (Deep Learning) strengthens meaningful learning experiences by integrating critical thinking, problem-solving, collaboration, digital literacy, and technology-assisted instruction. These curriculum transformations demonstrate Indonesia's continuous efforts to improve educational quality in response to changing societal and technological demands. The findings provide valuable insights for policymakers, educators, and curriculum developers in designing more adaptive and sustainable curriculum policies. The study also highlights the importance of comprehensive teacher training and effective policy dissemination to ensure successful curriculum implementation.